New insight into Acyclovir Renal Handling and Nephrotoxicity - Gunness, Patrina (2011)
Drug – induced nephrotoxicity is a serious adverse reaction that can have deleterious effects on a patient’s health and well-being. Acyclovir is an example of such an agent that causes the aforesaid effects. The drug induces severe nephrotoxicity in patients. The etiology of acyclovir – induced nephrotoxicity has not been fully elucidated. The overall objective of this thesis is to gain new insight into the pathogenesis of acyclovir – induced nephrotoxicity. Cytotoxicity studies showed that acyclovir induced human renal proximal tubular (HK-2) cell death, in vitro, and that the degree of this toxicity was significantly reduced by co-exposure to 4-methylpyrazole. The results suggest that acyclovir induces direct insult to human renal proximal tubular cells and the toxicity may be caused by the parent drug’s noxious acyclovir aldehyde metabolite. Transepithelial transport studies illustrated that acyclovir does not inhibit the transport of creatinine across porcine renal proximal tubular (LLC-PK1) or HK-2 cell monolayers. The results suggest that acyclovir does not inhibit the tubular secretion of creatinine in vitro, and possibly, in vivo, as well. Therefore, the abrupt, pronounced and transient elevations in the levels of plasma creatinine observed in patients may be solely and genuinely due to reduced GFR as a result of acyclovir – induced nephrotoxicity, and not to a tubular interaction between creatinine and acyclovir. Employing human embryonic kidney cells (HEK293) containing the full-length human ABCG2 gene encoding the wildtype ABCG2 amino acid sequence; cell accumulation studies showed that in the presence of the human breast cancer resistance protein (BCRP) inhibitor, fumitremorgin C (FTC), there was significant intracellular accumulation of acyclovir. The results suggest that acyclovir is a substrate for the efflux transporter and bears several potential implications with respect to the renal transport mechanisms and pathogenesis of the direct tubular damage induced by the drug. Synthesizing all the data, the results contribute to a better understanding of the pathogenesis of acyclovir – induced nephrotoxicity. Moreover, the research highlights the need for future studies that will aid in further elucidation of the underlying cell and molecular mechanism(s) of this toxicity and potential therapies for prevention of the direct renal tubular injury induced by the drug.